Efficiency of KPU and Bawaslu Regulations on Ad Hoc Agency Selection in the 2024 Election Process - Muhammad Ali Husain; Suparji Suparji; Yusup Hidayat (Jurnal Indonesia Sosial Teknologi, 2024)
Ad hoc organizers such as PPK, PPS, PPLN, KPPS, KPPSLN, Panwascam, PKD, Overseas Panwaslu, and TPS Supervisors are pioneers in the process of organizing elections in Indonesia. Therefore, the selection process carried out must be honest, fair, and independent to make ad hoc organizers professional and integrity. To create a professional election administration with integrity, regulations or guidelines are needed so that the ad hoc body has guidance in working so that the election administration carried out produces independent elections. The method in this writing is a qualitative descriptive method. The main data collection that the author uses in this article is a journal on Election Management. Article analysis uses analysis content. The result of this research informs us that in the ad hoc election body selection process, there are still several regulations issued by the KPU and BAWASLU that are still less efficient in the election ad hoc body selection process which results in the selected election organizers being less qualified. This article hoped to provide input on the process of holding elections in the following year.